Design of Bifunctional Nb/V Interfaces for Improving Reversible Hydrogen Storage Performance of MgH2. Issue 10 (21st August 2022) - Meng, Yang; Ju, Shunlong; Chen, Wei; Chen, Xiaowei; Xia, Guanglin; Sun, Dalin; Yu, Xuebin
Abstract : While MgH2 has been widely regarded as a promising solid‐state hydrogen storage material, the high operating temperature and sluggish kinetics pose a major bottleneck for its practical application. Herein, V4 Nb18 O55 microspheres composed of nanoparticles with size of tens of nanometers are fabricated to promote H2 desorption and absorption properties of MgH2, which results in the uniform formation of Nb/V interfaces based on a molecular scale during the reversible hydrogen storage process. It is experimentally and theoretically demonstrated that the uniform building of Nb/V interfaces not only preserves the ability of Nb in weakening Mg‐H bonds but also alleviates the strong adsorption capacity of metallic Nb toward hydrogen atoms, leading to a relative energy barrier for the whole dehydrogenation process of MgH2 of only 0.5 eV, which is 0.22 and 0.43 eV lower than that of Nb and V, respectively. As a result, under the addition of V4 Nb18 O55 microspheres, the onset H2 desorption temperature of MgH2 is decreased to 165 °C, 125 °C lower than that of bulk MgH2, and the complete hydrogenation of Mg could be realized even at room temperature, while almost no H2 adsorption is observed for bulk Mg at a high temperature of 50 °C. Abstract : The homogeneous building of Nb/V interfaces not only preserves the ability of Nb in weakening Mg‐H bonds but also alleviates the strong adsorption capacity of metallic Nb toward hydrogen atoms, which effectively lowers the relative energy required for the hydrogen desorption from MgH2 .